Experiências de integração da espiritualidade na clínica psicológica - Beneduzzi, Telma Maria (2012)
This qualitative research aims at understanding the trajectory and experience of two clinical psychologists with a solid education and extensive experience in the area, who tried to integrate spirituality to their clinical practice. They aggregated knowledge of the spiritual-religious universe by applying emerging approaches, not yet partially or entirely recognized as psychological theories by the Psychology official organs. It comprises an autobiographical study and an interview with a research collaborator. It is justified, and it is relevant because it falls into a niche of themes, which includes the relations of spirituality, religiosity and religion to psychology and their explicit integration into clinical practice. These themes need to be more widely studied and discussed in the Brazilian academic field of psychology. The data gathered and the data contained in the autobiography were related and categorized according to the axes that were selected for the analysis, which was undertaken with the support of the chosen theory. A possible way of understanding the trajectory and experience of the two clinical psychologists in this study was that the previously adopted psychological theories proved insufficient to explain their life experiences. Besides, there is the fact that the existing studies about psychology and spirituality, pursued under the traditional approaches, are usually not included in the formal education in psychology and are not sufficiently available to most Brazilian clinical psychologists, remaining unknown for a long time, as it was the case of this research collaborators